Characterization of permanent deformation resistance of precipitated calcium carbonate modified asphalt mixture - Moghadas Nejad, Fereidoon; Azarhoosh, Ali Reza; Hamedi, Gholam Hossein; Azarhoosh, Mohammad Javad (Journal of Civil Engineering and Management, 2015)
Rutting in asphalt pavements that appears as an indentation in the longitudinal direction continues to create problems for pavement agencies. This paper presents the results of the laboratory study on rutting susceptibility of asphalt mixtures containing Precipitated Calcium Carbonate (PCC) coated by a thin layer of a polymeric compound. To assess the impact of PCC on rutting properties of HMA, control mixtures (without PCC) and mixtures containing PCC were tested using dynamic creep and indirect tensile stiffness modulus tests. The HMA mixtures containing 0%, 5%, 10%, and 15% of PCC were prepared. In this paper, it is shown that the use of PCC can decrease the rutting potential of asphalt mixes. According to the results obtained in this study; using a 5% PCC in HMA is acceptable for heavy traffic volume roads especially in tropical regions.